The time traveler's wife [compact disc, unabridged] : a novel - Niffenegger, Audrey (HighBridge, 2005)
Clare first met her future husband, Henry, when he was 30 years her senior. However, as a result of Henry's Chrono-Displacement Disorder, when the couple married, they were only separated by eight years. Unable to stop shifting in time, Henry attempts to coup with the emotional trauma of missing and revisiting portions of his life.